Systematic literature review: Identifikasi miskonsepsi pada pembelajaran matematika - Ridho, Muhamat Hidayatul; Juandi, Dadang (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2023)
The Systematic Literature Review (SLR) discussed in this article is related to the identification of misconceptions in learning mathematics. A total of 26 articles used in this review were obtained from the ERIC and ProQuest databases with publication criteria in 2019 – 2023 and have met all predetermined study criteria. Procedures for systematic literature review include search strategy, selection criteria, selection process, data collection, and data analysis. The research results obtained include: 1) 2022 will be the peak of the development of the publication of articles related to mathematical misconceptions in reputable international journals with a total of 8 articles, 2) mathematical misconceptions are most widely researched at the Junior High School (SMP) level with 10 studies, 3) algebraic and number materials are the mathematical concepts that have been studied the most by misconceptions with the number of articles found 7 and 5 articles respectively, 4) the research on students' mathematical misconceptions is mostly carried out, especially in Indonesia and Turkey with the number of articles respectively 7 and 6 articles, 5) the most widely applied research method is the qualitative method with a total of 16 articles, 6) the forms of misconceptions found in this study are inadequate conceptions, over-generalizations, incorrect classification, and errors in definition.